2015
DOI: 10.1038/nbt.3095
|View full text |Cite
|
Sign up to set email alerts
|

Distributing a metabolic pathway among a microbial consortium enhances production of natural products

Abstract: Metabolic engineering of microorganisms such as Escherichia coli and Saccharomyces cerevisiae to produce high-value natural metabolites is often done through functional reconstitution of long metabolic pathways. Problems arise when parts of pathways require specialized environments or compartments for optimal function. Here we solve this problem through co-culture of engineered organisms, each of which contains the part of the pathway that it is best suited to hosting. In one example, we divided the synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
473
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 602 publications
(479 citation statements)
references
References 46 publications
4
473
0
2
Order By: Relevance
“…However, previous research on microbial consortia was primarily concerned with the study of mixed population stability and dynamic interactions (7)(8)(9)(10)(11), although a few recent studies have reported the engineering of microbial consortia for utilization of simple sugars to make small molecules of central carbon metabolism, such as ethanol and lactate (12,13). Progress was made recently, when a full n-butanol pathway was expressed in two separate E. coli cells to achieve higher production (14) and when a bacterium-yeast coculture was used to address the difficulties of functional reconstitution of a pathway involving prokaryotic and eukaryotic enzymes in a consortium, and thus improved production of complex pharmaceutical molecules (15). Here, we expand the generality of the coculture engineering by demonstrating that microbial cocultures can also be engineered to overcome more universal challenges in metabolic engineering, including high-level intermediate secretion and low-efficiency sugar mixture utilization.…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…However, previous research on microbial consortia was primarily concerned with the study of mixed population stability and dynamic interactions (7)(8)(9)(10)(11), although a few recent studies have reported the engineering of microbial consortia for utilization of simple sugars to make small molecules of central carbon metabolism, such as ethanol and lactate (12,13). Progress was made recently, when a full n-butanol pathway was expressed in two separate E. coli cells to achieve higher production (14) and when a bacterium-yeast coculture was used to address the difficulties of functional reconstitution of a pathway involving prokaryotic and eukaryotic enzymes in a consortium, and thus improved production of complex pharmaceutical molecules (15). Here, we expand the generality of the coculture engineering by demonstrating that microbial cocultures can also be engineered to overcome more universal challenges in metabolic engineering, including high-level intermediate secretion and low-efficiency sugar mixture utilization.…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…The rise of synthetic biology has provided access to larger synthetic DNA constructs, rapid DNA capture,7, 8, 9 editing,10, 11 assembly,12, 13 and other advances 14, 15. The prospect of using these new tools to assemble de novo biosynthetic pathways in well‐characterized heterologous host strains16, 17 for diversification and optimization of natural products, derived from less tractable microorganisms, is an attractive goal.…”
mentioning
confidence: 99%
“…After optimization of culture conditions, this microbial consortium produced 33 mg L −1 of oxygenated taxanes. [99] …”
Section: Coculture Strategiesmentioning
confidence: 99%
“…[99] Taxadiene is synthesized from GGPP by taxadiene synthase, and the following reaction for oxygenated taxanes biosynthesis requires cytochrome P450, which is hardly expressed in E. coli. Therefore, E. coli was used for overproducing taxadiene, since it was more feasible to direct the metabolic flux toward the product, and yeast was engineered for converting taxadiene to oxygenated taxanes for its higher capability of expressing eukaryotic P450 enzymes.…”
Section: Coculture Strategiesmentioning
confidence: 99%
See 1 more Smart Citation